2016
DOI: 10.1177/1524839916629970
|View full text |Cite
|
Sign up to set email alerts
|

Can Home-Based HIV Rapid Testing Reduce HIV Disparities Among African Americans in Miami?

Abstract: Sixty percent of African Americans have had an HIV test, yet this population disproportionately contributes to AIDS mortality, suggesting that testing is not occurring early enough to achieve optimal outcomes. OraQuick, the first Food and Drug Administration-approved home-based HIV rapid test (HBHRT) could potentially increase testing rates. We assessed whether community health workers (CHWs) paired with HBRHT could improve HIV screening and health care access among African Americans in Miami, Florida. In Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…We summarize key characteristics of included studies in Table 1 . Four studies (31%) were quasi-experimental (pre-post studies) [ 31 34 ]; three (23%) were experimental studies, including one non-randomized experimental study [ 35 ] and two controlled trials [ 36 , 37 ]. Six (46%) were cohort studies [ 38 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…We summarize key characteristics of included studies in Table 1 . Four studies (31%) were quasi-experimental (pre-post studies) [ 31 34 ]; three (23%) were experimental studies, including one non-randomized experimental study [ 35 ] and two controlled trials [ 36 , 37 ]. Six (46%) were cohort studies [ 38 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…A US study found that participants were more likely to complete an HIV self-test and get linked to care in the presence of a community health worker (e.g. respected peer in the community, familiar with cultural norms), compared to self-testing independently [ 24 ]. Various self-testing strategies are possible: supervised self-testing (set up self-testing kiosks in clinics or outreach community sites/vans), unsupervised self-testing (purchase of self tests from pharmacies or online sites, and provision of a toll free number for linkages to counselling and care) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…8,14,15 CHWs have demonstrated effectiveness in HIV prevention by encouraging people to know their HIV status, educating and testing diverse populations, reducing stigma, and linking people who test positive to health care. 4,[7][8][9][10]16,17 Given the demonstrated strengths and history of CHWs working in HIV prevention and care, CHWs could play a vital role in addressing STIs. In the STI field, CHWs could perform a range of tasks, including aiding in STI prevention and education, referring people to testing and treatment, and helping patients enter and navigate care.…”
Section: Potential Role Of Chws In the Sti Fieldmentioning
confidence: 99%
“…8,14,15 CHWs have demonstrated effectiveness in HIV prevention by encouraging people to know their HIV status, educating and testing diverse populations, reducing stigma, and linking people who test positive to health care. 4,7-10,16,17…”
Section: Potential Role Of Chws In the Sti Fieldmentioning
confidence: 99%
See 1 more Smart Citation